EP.TU.653Improving surgical admission clerking by introducing a standardized clerking proforma: a quality improvement project. (28th October 2021) - Geropoulos, Georgios; Kennedy, Clio; Tang, Stanley; Elhamshary, Ahmed; Rakhshani-Moghadam, Sara; Grant, Calum
Abstract: Aims: When clerking new admissions several critical actions must be performed in a timely and accurate way. These include reviewing referral letters, obtaining a detailed medical history and documenting the patient's plan. This is of paramount importance, especially in high volume surgical hospitals. The aim of this quality improvement project is to evaluate a standardized electronic proforma for surgical patient clerking in an attempt to minimize missing information that can compromise peri-operative care. Methods: A short questionnaire assessing the clerking process was handed out to doctors and allied health professionals. It was completed before and after the introduction of the clerking proforma. Proportion confidence intervals (95% CI) compared for each answer before and after the proforma releasing. Results: Domains with a statistically significant improvement were the admission reason, management, treatment escalation and venous thromboprophylaxis plan in patients on long term anticoagulation. After introduction of the proforma, feedback still implied that the social history needed to be more extensive. Further edits to the proforma in a second cycle include prompts regarding baseline function and ADLs, as well as existing packages of care. Conclusions: Overall, the introduction of the surgical patient clerking proforma lead to an improvement of the quality of the clerking as assessed by standardized questionnaires. It is noteworthy that a complete clerking is correlated with more effective handover between health care providers, less medical errors, less treatment delays and improved patient outcomes.